PENETRASI TANPA LABEL: PENDEKATAN BARU INTERNALISASI IDEOLOGI PANCASILA PADA GENERASI MILENIAL - Kuswandoro, Wawan Edi (Waskita: Jurnal Pendidikan Nilai dan Pembangunan Karakter, 2023)
This article describes millennial Pancasila discourse. Discourse on Pancasila is often combined with discourse on The New Order, ideology politicization, partisan ideology, practical political objectives, and other political discourses. The Pancasila animates citizenship discourse on life, ideology, and state. The discourse on Pancasila has a discursive dynamic that suggests discussion, from power parties using it for political propaganda to its alienation in social life, especially among the millennial age. The article uses Critical Discourse Analysis (CDA) method to analyze big data from Twitter, Facebook, YouTube, and Instagram hashtags for #Pancasila and #Millennial, scientific discourse in journals, and informants. MediaToolKit was used to mine besides informants from Java, Kalimantan, Sumatra, Bali, Nusa Tenggara, and Papua provided discourses and narratives. This research explores the Pancasila discourse among the millennial age and a novel technique of ideological penetration called "penetration without a label (Pental)" to internalize Pancasila philosophy